Guayaquil: Two waves - Muñoz, Othon (Revista Universidad de Guayaquil, 1984)
Guayaquil is like a river. The old waves are leaving. The high tides are coming. The current rises and falls. A disturbing flow of comings and goings continues... People also come and go. Customs change, gestures. And gestures, language. The neighbors also leave... Only the traces of that past remain, so close and so far at the same time, like seeds of the future scattered on the road... But we still have a generous way of being in Guayaquil. That Olympian frankness, and that contagious dynamism. We still have its extroverted, talkative, euphoric being. And its desire to shout, to run and to drink with enormous contagious joy. And, as it is a port open to the heart of life, the corridors of yesteryear navigate between a beer and the shipyard of its people...